Women Workers, Employment Policy and the State: The Establishment of the Ontario Women's Bureau, 1963-1970 - Sangster, Joan (Labour / Le Travail, 1995)
In 1963, the Ontario Government established a Women's Bureau within the Department of Labour to do research, public relations work, and policy development relating to working women in the province. This article examines the early evolution of the Women's Bureau from 1963 to 1970 assessing the reasons for its establishment and the successes and failures of its early programs designed to aid working women. The Bureau urged the government to consider anti-discrimination legislation, and in 1970 it helped to develop new legislation designed to enhance women's equality by legalizing maternity leave, banning discrimination based on marital status, and abolishing job posting by sex. Drawing on recent debates about the state and employment policy, particularly those looking at the relationship between feminist and labour activists and the state, this article asks whose interests the Bureau represented, and whether or not this state-initiated legislation designed to enhance gender equality was effective, either in the short or long term.
Keywords: DISCRIMINATION – Law & legislation; Equality; LABOUR/LE Travail (Book); ONTARIO – Politics & government; Ontario; Public Relations; Women employees